2020
DOI: 10.21203/rs.3.rs-26264/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compartmentalized mathematical model to predict future number of active cases and deaths of COVID-19

Abstract: In December 2019, China reported a series of atypical pneumonia cases caused by a new Coronavirus, called COVID-19. In response to the rapid global dissemination of the virus, on the 11th of Mars, the World Health Organization (WHO) has declared the outbreak a pandemic. In light of this situation, this paper intends to analyze and improve the current SEIR models to better represent the behavior of the COVID-19 and accurately predict the outcome of the pandemic in a given social, economic and political scenario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Genetic Algorithms (GA) have been successfully utilized to optimize the parameters of epidemiological models for the Severe Acute Respiratory Syndrome (SARS) ( Yan & Zou, 2008 ), cholera ( Akman & Schaefer, 2015 ; Akman, Corby & Schaefer, 2016 ) and recently for the SARS-CoV-2 outbreak ( Neto et al, 2020 ; Yousefpour, Jahanshahi & Bekiros, 2020 ; Kozio, Stanisawski & Bialic, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic Algorithms (GA) have been successfully utilized to optimize the parameters of epidemiological models for the Severe Acute Respiratory Syndrome (SARS) ( Yan & Zou, 2008 ), cholera ( Akman & Schaefer, 2015 ; Akman, Corby & Schaefer, 2016 ) and recently for the SARS-CoV-2 outbreak ( Neto et al, 2020 ; Yousefpour, Jahanshahi & Bekiros, 2020 ; Kozio, Stanisawski & Bialic, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…An inappropriate model will perform poorly even with the best possible parameter settings, same way as the the most appropriate model with badly chosen parameter values. Newer studies, such as Zhou et al (2020) , Liu et al (2020a) , Neto et al (2020) , and Kozio, Stanisawski & Bialic (2020) , validated the proposed modells on data, in order to verify the parameter estimations and prediction of the trend of SARS-CoV-2 infections.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of further deterministic and statistical COVID-19 SEIR models incorporating hospitalisation, intensive care and deaths can be found in [13,14,15]. However, again, all of these models use parameter estimates that are constant for all time, based upon figures within the literature.…”
Section: Covid-19 Modelsmentioning
confidence: 99%
“…Due to the rapid contagiousness of the virus (Hafeez et al, 2020), nearly every country employed measures against the virus’ spread, such as national lockdowns and restrictions of outdoor activities. The pandemic showed that statistical and machine learning modelling can potentially predict the number of new cases or deaths for a given country (Cássaro & Pires, 2020; Niazkar & Niazkar, 2020; Neto et al, 2020). The accurate forecast of the infection curve can facilitate government’s measures towards the suppression of the growth rate.…”
Section: Introductionmentioning
confidence: 99%